PHARMACIST’S ROLE IN MEDICATION RECONCILIATION TO PREVENT THE RISK OF MEDICATION ERROR AT BALI MANDARA HOSPITAL - Sutema, Ida Ayu Manik Partha; Maharjana, IBN (Journal Pharmaceutical Science and Application, 2021)
Background: Pharmacists have an important role in implementing drug reconciliation. The implementation of drug reconciliation allows the process of identifying drug administration errors due to information gaps, which we can avoid by optimizing information as early as possible at every shift in the process of providing health services through the reconciliation process. This process is crucial, especially for groups of patients with chronic diseases who have a high risk of changing health care delivery settings. Failure to identify results in errors in administering drugs that lead to worsening clinical conditions, resulting in increased service needs and health costs. Objective: Provides information about the tendency of pharmacists who work at the UPTD Bali Mandara General Hospital to reduce drug use errors through the drug reconciliation program. Methods: Thematic analysis of structured interview results. Results: Almost all participants (6 out of 8 pharmacists) tend to be willing to be involved in the drug reconciliation process. There are three main themes of consideration that underlie the tendency of pharmacists to be willing to be involved in the drug reconciliation process, namely, related to understanding the definition, purpose, and consistency of the implementation of reconciliation. In controlling the incidence of medication errors, the biggest preventable errors through medication reconciliation are drug duplication and drug discrepancy. Conclusion: The tendency for pharmacists to be involved is good, and the tendency to control the risk of medication errors is still lacking in terms of communication and consistency in filling out by all officers. Keywords:  Pharmacist’s role, drug reconciliation, risk of medication errors